UJI DAYA HAMBAT DAUN PEGAGAN (CENTELLA ASIATICA) TERHADAP BAKTERI ESCHERICHIA COL - Situmorang, Imelda; Nasution, Irma Riavael; Manalu, Mentari Trinolina (STKIP Subang, 2025)
Escherichia coli is a Gram-negative bacterium that frequently causesgastrointestinal infections and remains a public health concern due to increasingantimicrobial resistance. This condition encourages the exploration of herbal plantsas alternative antibacterial agents. Centella asiatica (pegagan) is a medicinal plantwidely used in traditional medicine and is known to contain bioactive compoundssuch as flavonoids, tannins, saponins, and triterpenoids that potentially exhibitantibacterial activity. This study aimed to evaluate the inhibitory effect of ethanolicextract of C. asiatica leaves against E. coli using the disc diffusion method. Freshpegagan leaves were processed into simplicia, extracted with 96% ethanol, anddiluted into four concentrations (15%, 30%, 45%, and 60%). Escherichia colicultures were standardized to 0.5 McFarland and inoculated onto agar media. Paperdiscs impregnated with each extract concentration were applied, with ciprofloxacinused as a positive control and ethanol as a negative control. After incubation at 37°Cfor 24 hours, inhibition zones were measured. The results showed that none of theextract concentrations produced a measurable inhibition zone, while ciprofloxacinformed a clear zone of inhibition, indicating bacterial sensitivity and method validity.These findings suggest that ethanolic extract of C. asiatica leaves at concentrationsof 15–60% does not exhibit measurable antibacterial activity against E. coli, possiblydue to insufficient concentration of active compounds to penetrate the Gramnegative bacterial cell wall.